CYBERSECURITY OF MEDICAL SYSTEMS: CHALLENGES AND SOLUTIONS IN THE CONTEXT OF THE INTERNET OF THINGS - Анастасія Андріївна Стрєлкина; Дмитро Дмитрович Узун (Радіоелектронні і комп'ютерні системи, 2017)
This article reviews the main challenges and solutions in the field of cybersecurity medical systems in the context of the Internet of things. The authors identified key vulnerabilities, threats and risks of health care network devices. The paper describes in general terms the main regulatory documents in the field of cybersecurity providing, such as HIPAA privacy and security rules, FDA requirements for cybersecurity for pre- and post-market of the medical devices. Using the results of research authors systematized basic directions in providing cyber security of medical devices in the context of Internet of things